Pelaksanaan Akad Ijarah Dalam Sewa-Menyewa Kamar Hotel Pada Hotel Syariah Al-Jayri Medan - Alwi, Muhammad; Sugianto, Sugianto (-, 2023)
This study aims to determine the implementation or implementation of the ijarah contract in hotel room rentals at the Al-Jayri Syariah Hotel Medan.what is the mechanism for implementing the ijarah contract (lease) at the al-Jayri sharia hotel in Medan is the implementation of the ijarah contract (leasing) at the al-jayri sharia hotel in accordance with the DSN-MUI fatwa,The ijarah contract is a lease agreement carried out by both parties who have a contract between mu'ajir (the person who rents out) and musta'jir (the person who rents) both parties take advantage of the existence of a rental substitute. Then this study aims to determine the mechanism of the implementation of the ijarah contract and the suitability of the ijarah contract (lease) with the DSN-MUI Fatwa. The type of this research is qualitative the method used in data collection was obtained from documentation and interviews. Sources of data used in this study are primary data and secondary data. This type of research includes field research. The results obtained are that the implementation of the ijarah contract in the practice of renting a hotel room at the Syariah Hotel Al-Jayri Medan. carried out based on an agreement between the two parties, namely between the hotel (receptionist) and the room tenant by paying rent to the hotel according to the price agreed by both parties. And the suitability of the ijarah contract in the practice of renting hotel rooms at the Al-Jayri Syariah Hotel is in accordance with the DSN-MUI Fatwa regarding ijarah with the fulfillment of the pillars and conditions of ijarah.